The C20orf133 gene is disrupted in a patient with Kabuki syndrome - Maas, Nicole M C (BMJ Group, 2007)
BACKGROUND: Kabuki syndrome (KS) is a rare, clinically recognisable, congenital mental retardation syndrome. The aetiology of KS remains unknown. METHODS: Four carefully selected patients with KS were screened for chromosomal imbalances using array comparative genomic hybridisation at 1 Mb resolution. RESULTS: In one patient, a 250 kb de novo microdeletion at 20p12.1 was detected, deleting exon 5 of C20orf133. The function of this gene is unknown. In situ hybridisation with the mouse orthologue of C20orf133 showed expression mainly in brain, but also in kidney, eye, inner ear, ganglia of the peripheral nervous system and lung. CONCLUSION: The de novo nature of the deletion, the expression data and the fact that C20orf133 carries a macro domain, suggesting a role for the gene in chromatin biology, make the gene a likely candidate to cause the phenotype in this patient with KS. Both the finding of different of chromosomal rearrangements in patients with KS features and the absence of C20orf133 mutations in 19 additional patients with KS suggest that KS is genetically heterogeneous.